Cross-sectoral Analysis of 1.4 Million AOK-insured Patients with Back Pain in Baden-Württemberg – What Influence does Outpatient Specialist Care Have? - Jansen, Tom R.; Endres, Heinz; Barnewold, Lina; Kaufmann-Kolle, Petra; Knapstein, Sabine; Strauss, Andreas Christian; Flechtenmacher, Johannes; Lembeck, Burkhard (Zeitschrift für Orthopädie und Unfallchirurgie, 2021)
Background Back pain is one of the leading causes of disability globally and the most common musculoskeletal pain in Germany. The lifetime prevalence of back pain ranges from 74% to 85%, and the point prevalence ranges from 32% to 49%. One in five individuals with statutory health insurance visits a doctor at least once a year for back pain, and 1 in 20 individuals is on sick leave at least once a year. The question as to what extent can different outpatient care concepts substantially contribute to improving care and avoiding inpatient hospital treatment has repeatedly been the subject of controversial political discussions. This study aimed to present a description of the reality of care in Baden-Württemberg (BW), Germany, based on claims data.Material and Methods Anonymised routine billing data of AOK Baden-Württemberg were analysed in compliance with data protection regulations. The billing data cover the outpatient and inpatient care sectors. All AOK patients in BW who received at least one ICD10 diagnosis from their physician in the first half of 2015 were considered for the analysis. Patients with at least one diagnosis of back pain were evaluated as patients with back pain, whereby the assignment to the diagnosis group of specific or non-specific back pain was made based on the code.Results In the first half of 2015, nearly 988 925 patients with back pain were registered in the 6696 primary care clinics in BW, approximately 302 524 patients in 1172 orthopaedic clinics and 17 043 patients in 89 neurosurgical clinics. Primary care clinics reported back pain diagnosis in 34.6%, orthopaedic clinics in 51.9% and neurosurgical clinics in 78.6% of cases. Primary care clinics diagnosed a specific cause in approximately one-third of patients with back pain, orthopaedic clinics in approximately 40% of their patients and neurosurgery clinics in one in two cases. Overall, approximately 1.2% of 1.3 million patients with back pain (January to December 2015 in BW) were hospitalised. Inpatient therapy consisted of surgical therapy and conservative therapy. Nucleotomy, decompression and spondylodesis were the three most common surgical procedures performed. Pain medication and remedy prescriptions decreased pain after spinal surgery. There are significant regional differences in referral and surgery rates. The mean inpatient referral rate was 535 of 100 000 AOK insurants, and the median was 536 of 100 000 AOK insurants. The mean surgery rate among all admitted patients with back pain was 49.9%, and the median was 49.8%.Conclusion The vast majority of patients with back pain are treated as outpatients. Only approximately 1.2% of all patients with back pain were treated as inpatients in 2015. Of these, approximately half underwent surgery. Spinal surgeries led to a decrease in pain medication and remedy prescription postoperatively. The three most frequent surgical procedures were ‘decompression’, ‘excision of disc tissue’ and ‘spondylodesis’. There were significant regional differences.
Keywords: back pain; conservative therapy; surgical therapy; claims data; spine